Extranodal Marginal Zone Lymphoma of Mucosa-Associated Lymphoid Tissue of the Salivary Glands: A Multicenter, International Experience of 248 Patients (IELSG 41). (12th August 2015) - Jackson, Amie E.; Mian, Michael; Kalpadakis, Christina; Pangalis, Gerassimos A.; Stathis, Anastasios; Porro, Elena; Conconi, Annarita; Cortelazzo, Sergio; Gaidano, Gianluca; Guillermo, Armando Lopez; Johnson, Peter W.; Martelli, Maurizio; et al.
Abstract: Background: The salivary gland is one of the most common sites involved by nongastric, extranodal marginal zone lymphomas of mucosa-associated lymphoid tissue (MALT). A large series of patients with long-term follow-up has not been documented. This multicenter, international study sought to characterize the clinical characteristics, treatment, and natural history of salivary gland MALT lymphoma. Methods: Patients with biopsy-confirmed salivary gland MALT lymphoma were identified from multiple international sites. Risk factors, treatment, and long-term outcomes were evaluated. Results: A total of 247 patients were evaluated; 76% presented with limited-stage disease. There was a history of autoimmune disorder in 41%, with Sjögren disease being the most common (83%). Fifty-seven percent of patients were initially treated with local therapy with surgery, radiation, or both; 37 of patients were treated with systemic therapy initially, with 47% of those receiving rituximab; and 6% of patients were observed. The median overall survival (OS) was 18.3 years. The median progression-free survival (PFS) following primary therapy was 9.3 years. There was no difference in the outcomes between patients receiving local or systemic therapy in first-line management. On multivariate analysis, age <60 years and low to intermediate international prognostic index were associated with improved OS and PFS; Sjögren disease was associated with improved OS. Conclusion: Salivary gland MALT lymphoma has an excellent prognosis regardless of initial treatment, and patients with Sjögren disease have improved survival. Risks for long-term complications must be weighed when determining initial therapy. Implications for Practice: Patients with salivary gland extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) have an excellent prognosis, particularly those with associated Sjögren's disease. A wide range of available therapies may provide similar durable rates of disease control and survival. Therefore, an important goal in selection of therapy should be to minimize morbidity from treatment. When determining initial therapy for these patients, practitioners should consider the potential side effects and long-term toxicities of treatment. Abstract : This multicenter, international study sought to characterize the clinical characteristics, treatment, and natural history of salivary gland MALT lymphoma in 247 patients. There was no difference in the outcomes between patients receiving local or systemic therapy in first-line management. On multivariate analysis, age less than 60 years and low to intermediate international prognostic index were associated with improved overall survival and progression-free survival; Sjögren disease was associated with improved overall survival.